O cinema fantástico no Rio Grande do Sul (1960-2020) - Nunes, Rodrigo Figueiredo (2021)
This paper aims to pinpoint and analyse the different manifestations of the fantastic genre produced in the State of Rio Grande do Sul from 1960 to 2000. The proposal embodies all possible production formats (film, VHS, digital) with their respective length of time (short, average and long movies). The definition of fantastic is brought up by authors such as Tzvetan Todorov (1975), Gérard Lenne (1974) and David Roas (2014). The report makes use of the documental methodology, as defined by the likes of Antônio Gil (2002) and Antônio Severino (2007). Interviews with the filmmakers in charge of such works were carried out with the due authorization of the Ethics Commitee for Research of PUCRS (Pontifícia Universidade Católica do Rio Grande do Sul). Altogether, 165 fantastic audiovisual films made in Rio Grande do Sul were found, and each one was added to its appropriate thematic category (human horror, monsters, the unkown, fantasy, dead people related, psychological terror, science fiction, alternate worlds, double evils, myths or legends of Rio Grande do Sul and anthologies). Open to multiple interpretations, the works allow for a critical outlook on the “gaúcha” (local) society.